2000
DOI: 10.2307/3435058
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Seven Urinary Phthalate Metabolites in a Human Reference Population

Abstract: Dialkyl or alkyl aryl esters of 1,2-benzenedicarboxylic acid, commonly called phthalates, are ubiquitous industrial chemicals with a wide range of chemical and toxicologic characteristics. Phthalates are used primarily as plasticizers in flexible polyvinyl chloride (PVC) products such as blood bags and children's toys. Nonpolymeric uses of phthalates as fixatives, detergents, lubricating oils, and solvents lead to their inclusion in numerous and diverse products such as cosmetics and wood finishes. The widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
148
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(154 citation statements)
references
References 22 publications
4
148
1
1
Order By: Relevance
“…In view of these findings, it is particularly concerning that women of childbearing age had significantly higher urinary concentrations of MBP than women in other age groups (90). However, other studies did not find a significant difference between women of reproduc-tive age (age 20-39 yr) and younger or older females but confirmed that women of all ages had higher urinary concentrations of MBP, MEP, and MBzP compared with men (88,92).…”
Section: Relevance To Humansmentioning
confidence: 88%
See 3 more Smart Citations
“…In view of these findings, it is particularly concerning that women of childbearing age had significantly higher urinary concentrations of MBP than women in other age groups (90). However, other studies did not find a significant difference between women of reproduc-tive age (age 20-39 yr) and younger or older females but confirmed that women of all ages had higher urinary concentrations of MBP, MEP, and MBzP compared with men (88,92).…”
Section: Relevance To Humansmentioning
confidence: 88%
“…It has been proposed that the unconjugated monoesters are the mediators of reproductive toxicity in rats (141) because monoesters undergo little glucuronidation in these animals. Conversely, in humans, the majority of phthalate monoesters and even the secondary metabolites are present in urine in the form of glucuronides (89,90). In serum, the metabolites Clinical Reviews in Allergy & Immunology Volume 31, 2006 (at least of MEHP) were reported to be mostly conjugated (89), but this is in marked contrast to the findings from a single human volunteer (142).…”
Section: Relevance To Humansmentioning
confidence: 97%
See 2 more Smart Citations
“…When urinary MBP was used as biomarker to assess DBP exposure in human volunteers, detection of DBP metabolites provided evidence for environmental exposure and biotransformation in vivo, whereas detection of the parental compound in urine has been considered to be an indication of environmental contamination (Duty et al 2005;Silva et al 2004Silva et al , 2003Blount et al 2000). Bacteria such as Burkholderia cepacia have the ability to grow on phthalates.…”
Section: Introductionmentioning
confidence: 99%